Layered multiple scattering approach to Hard X-ray photoelectron diffraction: theory and application - Trung-Phuc Vo; Olena Tkach; Sylvain Tricot; Didier Sébilleau; Jürgen Braun; Aki Pulkkinen; Aimo Winkelmann; Olena Fedchenko; Yaryna Lytvynenko; Dmitry Vasilyev; Hans-Joachim Elmers; Gerd Schönhense; et al. (npj Computational Materials)
Abstract Photoelectron diffraction (PED) is a powerful technique for resolving surface structures with sub-angstrom precision. At high photon energies, angle-resolved photoemission spectroscopy (ARPES) reveals PED effects, often challenged by small cross-sections, momentum transfer, and phonon scattering. X-ray PED (XPD) is not only an advantageous approach but also exhibits unexpected effects. We present a PED implementation for the spin-polarized relativistic Korringa-Kohn-Rostoker (SPRKKR) package to disentangle them, employing multiple scattering theory and a one-step photoemission model. Unlike conventional real-space approaches, our method uses a k-space formulation via the layer-KKR method, offering efficient and accurate calculations across a wide energy range (20-8000 eV) without angular momentum or cluster size convergence issues. Additionally, the alloy analogy model enables simulations of finite-temperature XPD and effects in soft/hard X-ray ARPES. Applications include modeling circular dichroism in angular distributions (CDAD) in core-level photoemission of Si(100) 2p and Ge(100) 3p, excited by 6000 eV photons with circular polarization.